1997
DOI: 10.1093/toxsci/36.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emulphor, an Emulsifier, on the Pharmacokinetics and Hepatotoxicity of Oral Carbon Tetrachloride in the Rat

Abstract: Emulphor, a polyethoxylated vegetable oil, is now being used widely to incorporate volatile organic compounds (VOCs) and other lipophilic compounds into aqueous solutions for biochemical, pharmacokinetic, and toxicological studies. Previous work in this laboratory demonstrated that 0.25% Emulphor did not alter the kinetics or hepatotoxicity of low doses of CCL, compared to when the halocarbon was given to rats orally in water. The present study was undertaken as there was concern that higher concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…This might be because CCl 4 intoxication is a major source of free radical production in numerous organs, including the liver, kidneys, lungs, brain, and blood [ 50 ]. It has also been observed that following CCl 4 injection in rats, the concentration of CCl 4 is distributed more evenly in the kidneys than in the liver [ 51 ], since the kidney has a high affinity for CCl 4 and contains cytochrome P450, predominantly in the cortex. The most common free radicals from CCl 4 are trichloromethyl radical (CCl 3 • ) and trichloromethyl peroxyl radical (CCl 3 O 2 • ) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This might be because CCl 4 intoxication is a major source of free radical production in numerous organs, including the liver, kidneys, lungs, brain, and blood [ 50 ]. It has also been observed that following CCl 4 injection in rats, the concentration of CCl 4 is distributed more evenly in the kidneys than in the liver [ 51 ], since the kidney has a high affinity for CCl 4 and contains cytochrome P450, predominantly in the cortex. The most common free radicals from CCl 4 are trichloromethyl radical (CCl 3 • ) and trichloromethyl peroxyl radical (CCl 3 O 2 • ) [ 52 ].…”
Section: Discussionmentioning
confidence: 99%